Reversible superdeformability of hiPSC epithelial cortinoids - Anirban Jana; Justin Tauber; Adeline Boyreau; Basile Gurchenkov; Gaëlle Recher; Maxime Feyeux; Kevin Alessandri; Pierre Nassoy; L. Mahadevan (Proceedings of the National Academy of Sciences, 2026)
Epithelial cortinoids, fluid-filled shells formed from induced pluripotent stem cells (iPSCs), must accommodate large deformations during growth and morphogenesis. Using inflation–deflation assays and high-resolution imaging, we find that these fluid-filled shells are weakly pressurized and achieve extreme deformability through reversible soft modes of deformation accommodated by the cytoskeleton. We show that cytoskeletal elements such as actin localized along lateral cell edges undergo tilt and bend instabilities that buffer mechanical load by decoupling apico–basal stretching from lateral extension. These reversible instabilities act as elastic safety valves, permitting large shape changes without loss of epithelial hydraulic and topological integrity. A minimal theoretical and computational model demonstrates how tilt and bend reduce effective resistance to radial thinning and explains the observed pressure–strain softening. Thus, iPSC shells exploit reversible cytoskeletal instabilities as mechanical buffers, enabling robust tolerance of large deformations in developing epithelia.